The Labour Market Value of Liberal Arts and Applied Education Programs: Evidence from British Columbia - Adamuti-Trache, Maria; Hawkey, Colleen; Schuetze, Hans G.; Glickman, Victor (Canadian Journal of Higher Education, 2006)
In this article, labour market outcomes of British Columbia graduates from liberal arts and applied education programs are investigated by examining the 1996 cohort of baccalaureate graduates one year and five years after graduation. We argue that the individual return to education has to be analyzed from a multi-dimensional perspective, in relation to initial educational and career goals of graduates who have anticipated both intellectual challenges and economic rewards from their investment in education. The study reveals differences in outcomes (i.e., employment, earnings) by program type, gender and age. Our main conclusion is that graduates from applied education programs experience a more rapid integration into the labour market as compared to graduates from liberal arts education programs. Although earning differences by program type and age either decrease or even disappear over time, earning differences by gender are enhanced five years after graduation. Also, we conclude that graduates from applied education programs establish and accomplish more focused educational and career goals, while graduates from liberal education programs establish broader educational and career goals.